CYP2D6 (G1934A) Gene Polymorphism in Rice Farmers with Long-term Pesticide Exposure, Suphan Buri, Thailand - Tanunchanok Pitaksilp1 , Kampol Ruchiwit2 , Kowit Suwannahong3 , Wanida Pongstaporn4 , Yuttana Sudja (Indian Journal of Forensic Medicine & Toxicology, 2020)
CYP2D6 G1934A (rs 3892097) gene polymorphism in coding region is leads to catalytic rate of cytochromeP450 enzyme activity toward xenobiotic, including insecticide. Study was aimed to investigate CYP2D6(G1934A) gene polymorphism in rice farmers along with occupational health risks and behaviors; and toevaluate the relationship of gene polymorphisms and serum cholinesterase (SChE) levels. Cross-sectionalstudy was carried out from June 2019 to February 2020. Data had collected from health service programby U-Thong district health promoting hospital. Gathered information concerning of pesticide exposuresfrom 50 rice farmers and 50 control respondents was conducted by questionnaire interviewing. Eachserum sample was determined SChE activity test by paper test and automatic analyzer; and EDTA bloodwas analyzed genotyping by PCR-RFLP. Chi-square was used to analyze on the different of personalinformation; and of polymorphism. Person correlation was evaluated relationship between SChE level andgenotypes. 60% of rice farmers were used pesticide over 10 years. Means of SChE level of both groupswere within reference value and significantly different (p = 0.033). Polymorphisms were included wild type(GG), heterozygote (GA) and homozygote (AA); and were significantly different between rice farmers andcontrol (p = 0.0001). GA genotype in rice farmers was more frequent and AA genotype was not detected.Relationship of polymorphism and SChE level were negative correlated (r = -0.258; p = 0.009). CYP2D6gene polymorphism may useful biomarker for duties assignments in agricultural workers especially riskgroup (GA genotype).